188k views
3 votes
Solve the system of equations using substitution. y = x + 6 y = –2x – 3 (4, –11) (1, 7) (–3, 3)

2 Answers

4 votes

Answer:

the top answer is correct it is -3,3

Explanation:

User Josh Jolly
by
5.2k points
4 votes
the answer to the question
Solve the system of equations using substitution. y = x + 6 y = –2x – 3 (4, –11) (1, 7) (–3, 3)-example-1
User ASMUIRTI
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.